Comparison of Clinical Outcomes between Salvage and Elective Thoracic Endovascular Aortic Repair in Patients with Advanced Esophageal Cancer with Aortic Invasion: A Retrospective Cohort Study - Sian-Han Lin; Jang-Ming Lee; I-Hui Wu (Biomedicines, 2021)
Aortoesophageal fistula (AEF) caused by esophageal cancer (EC) is a rare but life-threatening complication. However, the optimal management strategy remains undetermined. Previous cases have demonstrated that thoracic endovascular aortic repair (TEVAR) is effective for prophylactic management. In our study, we evaluated the management of AEF with elective TEVAR over salvage TEVAR. In our single-center retrospective cohort study, forty-seven patients with cT4M0 EC were included in this study, and we divided them into salvage (Group S) and elective (Group E) groups based on whether TEVAR was performed before the hemorrhagic AEF occurred. Our study outcomes included survival and complication rate after TEVAR. Group E showed better overall 90-day survival and aortic-event-free survival in 90-day and 180-day over Group S. More patients in Group E could receive subsequent chemoradiotherapy or esophagectomy. Significantly fewer AEF-related complications, including recurrent hemorrhagic events after TEVAR, hypoperfusion-related organ injury, and bloodstream infection, were noted in Group E. In patients with advanced EC-invading aorta, elective TEVAR offered an early overall and aortic-event-free survival benefit compared to salvage TEVAR. By reducing the AEF-related complications, elective TEVAR could provide more patients receiving subsequent curative-intent treatment.